CT Guided TTNA and Core Biopsy in Suspected Lung Cancer, Review of Cases in Adam Malik General Hospital, Medan - Hadi Suhendra; Fajrinur Syarani; Syamsul Bihar; Putri Chairani Eyanoer (Respiratory Science, 2021)
ounds: The cytological and histopathological findings establish the type of lung cancer cells as the definitive diagnosis of lung cancer. This study aimed to determine the characteristics of lung cancer patients in terms of age, mean age, gender, staging, the proportion of lung cancer cells by cytologic examination of Transthoracic Needle Aspiration (TTNA) and histopathologic evaluation from CT-guided core biopsy. Method: This is a descriptive study involving 42 subjects diagnosed with lung cancer at H. Adam Malik Hospital Medan in 2016-2020 that met the inclusion criteria through consecutive sampling. Data was analysed using descriptive statistics for categorical variables. Results: Of 42 study subjects, the 60–71-year age group had the highest percentage of lung cancer (42.9%). Male (71.4%) was higher than female, the most common lung cancer staging was IVA (57.1%), and adenocarcinoma was found to be the most frequent type of lung cancer in both cytology (33.3%) and histopathology (31.0%). Conclusion: We concluded that core biopsy is superior in diagnosing lung cancer compared to TTNA.